Fibroblast Growth Factor 21 Ameliorates NaV1.5 and Kir2.1 Channel Dysregulation in Human AC16 Cardiomyocytes - Li, Jiamin; Li, Yuanshi; Liu, Yining; Yu, Hang; Xu, Ning; Huang, Di; Xue, Yadong; Li, Sijia; Chen, Haixin; Liu, Jiali; Li, Qingsui; Zhao, Yiming; et al. (Frontiers in Pharmacology, 2021)
Infarcted myocardium is predisposed to cause lethal ventricular arrhythmias that remains the main cause of death in patients suffering myocardial ischemia. Liver-derived fibroblast growth factor 21 (FGF21) is an endocrine regulator, that exerts metabolic actions by favouring glucose and lipids metabolism. Emerging evidence has shown a beneficial effect of FGF21 on cardiovascular diseases, but the role of FGF21 on ventricular arrhythmias following myocardial infarction (MI) in human has never been addressed. This study was conducted to investigate the pharmacological effects of FGF21 on cardiomyocytes after MI in human. Patients with arrhythmia in acute MI and healthy volunteers were enrolled in this study. Serum samples were collected from these subjects on day 1 and day 7-10 after the onset of MI for measuring FGF21 levels using ELISA. Here we found that the serum level of FGF21 was significantly increased on day 1 after the onset of MI and it returned to normal on day 7-10, relative to the control samples. In order to clarify the regulation of FGF21 on arrhythmia, two kinds of arrhythmia animal models were established in this study,The results showed that the incidence and duration time of ischemic arrhythmias in rhbFGF21-treated MI rats were significantly reduced at different time point after MI compared with normal saline treated MI rats. Moreover, the onset of the first ventricular arrhythmias was delayed and the numbers of VF and maintenance were attenuated by FGF21 compared to the rhbFGF21 untreated group in ouabain model. Consistently, in vitro study also demonstrated that FGF21 administration was able to shorten action potential duration (APD) in hydrogen peroxide treated AC16 cells. Mechanically，FGF21 can ameliorate the electrophysiological function of AC16 cells, which is characterized by rescuing the expression and dysfunction of cardiac sodium current (INa) and inward rectifier potassium (Ik1) in AC16 cells induced by hydrogen peroxide. Moreover, the restorative effect of FGF21 on NaV1.5 and Kir2.1 was eliminated when FGF receptors were inhibited. Collectively, FGF21 has the potential role to ameliorate transmembrane ion channels remodeling through NaV1.5/Kir2.1 pathway by FGF receptors and thus reduce life-threatening post-infarcted arrhythmias, which provides new strategies for antiarrhythmic therapy in clinics.